RISK MANAGEMENT OF RICE SUPPLY CHAIN BASED ON RISK CORRELATION (Case Study: Penajam Paser Utara) - Aruni An Umila Ullya; Anggriani Profita; Farida Djumiati Sitania (Center for Study and Journal Management FTI UMI, 2022)
Rice is the staple food with a continuous increase of it’s demand. Therefore, it’s availability should be well-maintained. Rice farmers and millers don’t yet have an advantageous position. Other risks also has the potential to disrupt the rice production process. This study aims to analyze and create priority risk mitigation in the rice supply chain of PPU. The methods used in this research were ISM to create a risk structure, FMECA to assess risk, and AHP to mitigate priority risk. There were 41 risks, consist of 26 risks for farmers and 15 risks for millers. Based on FMECA result, the priority risk from farmers is poor quality rice seeds (RPN of 112 and a medium criticality level). The priority risk from millers is damage to the rice grinder machine (RPN of 490 and a very high criticality level). The mitigation strategies were prepared by considering the interrelationships between risks in the ISM. If totaled based on the results, there were 11 risks for farmers that could be overcome by the 6 alternative mitigation strategies that exist. As for the rice mill, there were 6 risks that could be overcome by the 4 alternative mitigation strategies that exist. All of these alternatives were calculated using the AHP method. The priority mitigation for the farmer's were routine monitoring and maintaining the moisture content of the seeds, while the priority mitigation for the millers were periodic maintenance scheduling and the provision of spare engine components.